Parton distributions and small-x QCD at the large hadron electron collider - Rojo, J; Caola, F (2009)
The proposed Large Hadron Electron Collider (LHeC) at CERN would bring Deep- Inelastic scattering into the unexplored TeV regime. The LHeC rich physics program, among other topics, includes both precision SM measurements to complement LHC physics as well as studies of QCD in the high energy limit. The present contribution reports on ongoing studies within the NNPDF framework towards the LHeC CDR. We study the impact of LHeC simulated data on PDF uncertainties, in particular the small- x gluon. We also assess the LHeC potential to disentangle between various scenarios of small-x QCD, including saturation models and small-x resummation. Finally, we explore how deviations from DGLAP can be quantified in inclusive measurements.